Improve the Ability to Recognize Vowal Letters through the Media Sand Paper Letter Modification in Deaf Children - Berlina Anisa Putri; Zulmiyetri Zulmiyetri (Edumaspul: Jurnal Pendidikan, 2024)
This study aims to improve the ability to recognize vowel letters through Modified Letter sandpaper media for deaf children in class VI at SLB Negeri 1 Pagaruyung. This research uses Single Subject Research & experimental research type with A-B design. Data collection in this study was carried out by observation, question and answer & trial. Data collection tools use percentages. The research output guidelines are described through graphs. Based on the research output, it can be seen that the ability to recognize vowel letters of deaf children increases after using modified sandpaper letter media. So it can be concluded that the modified sandpaper letter media can improve the ability to recognize vowel letters in deaf children in class VI at SLB Negeri 1 Pagaruyung.